A multi-spectroscopic study of chitosan-ovalbumin supramolecular structures formed at different pHs - Milião, Gustavo Leite (2019)
Proteins and polysaccharides are important biomolecules used in food because of their techno- functional properties as thickening, gelling and, in the case of proteins, emulsifiers/foaming agents. However, proteins are unstable at extreme processing conditions (high temperatures, presence of organic solvents and proteolytic agents), which limits their application in food formulations. An alternative to overcome this problem is the use of supramolecular structures from protein-protein and protein-polysaccharides interactions. In this research, the latter type of association was investigated. Protein-polysaccharide associative interactions allow the formation of supramolecular structures, which, in turn, present even better biological and physicochemical features, making the study of such chemical species, especially in a molecular basis, relevant for a variety of applications. However, research about the association of the protein ovalbumin (OVA) and the polysaccharide chitosan (CHS), is still scarce, especially in the food science field. Then, OVA-CHS interaction in aqueous solution of chloride acid, at different pH values (4.0 and 6.0), was studied in order to evaluate if the polysaccharide presence would cause any expressive conformational changes in the overall protein structure. Therefore, a multi-spectroscopic approach, using UV-Vis and fluorescence to analyze the tertiary structure of OVA, conjointly with FT-IR and circular dichroism to study possible secondary structure modifications, was undertaken. UV-Vis and fluorescence results showed that the biomolecules interacted at some molecular level, forming complexes without a major modification in the microenvironment polarity of the protein. Furthermore, the fluorescence analysis suggested that the quenching mechanism of chitosan is likely static. Moreover, CD and FT-IR spectroscopies revealed that changes in the secondary structure of OVA upon interacting with CHS depended on the concentration of the polysaccharide. This study showed that the biomolecules could interact at both pH values forming complexes that could be applied in food, pharmaceutical, and medical applications. Such research allowed the comprehension of basic and advanced science, which contributed to the researchers’ professional and (most important) human resource development. Keywords: Protein. Polysaccharide. Interaction. Spectroscopies. Supramolecular structures.